CSR Strategy of The Oil and Gas Industry to Enhance the Wellbeing of Coastal Communities Amid Climate Change: A Case Study of PT Pertamina Gas Operation West Java Area in Juntinyuat, Indramayu - Ayodya, Fabian Panji Ayodya; Vany Ardianto; Yedo Kurniawan (Indonesian Journal of Social Responsibility Review (IJSRR), 2024)
Climate change exerts multifaceted and profound adverse effects on coastal ecosystems, with Juntinyuat Village, located in Indramayu Regency, serving as a case study of impacted regions. Key consequences include accelerated coastal erosion and the escalation of high wave intensity, both of which pose escalating risks to the livelihoods of populations engaged in tourism, agriculture, and small-scale enterprises. This study aims to analyse the mitigation program implemented through the Corporate Social Responsibility (CSR) approach of PT Pertamina Gas Operation West Java Area (OWJA) with the "Perisai Jaga Bumi" program. This program involves various community groups in disaster mitigation efforts through mangrove conservation, economic empowerment of vulnerable communities, and the preservation of local culture and wisdom. The study's results show that integrating natural and cultural potential in the CSR strategy can strengthen community resilience against climate change impacts in terms of environment, society, and economy, while also promoting sustainable development in disaster-prone coastal areas. This program is expected to serve as a reference for other regions with similar conditions in Indonesia.